2012
DOI: 10.1016/j.pain.2012.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Afferent drive elicits ongoing pain in a model of advanced osteoarthritis

Abstract: Osteoarthritis (OA) is a chronic condition characterized by pain during joint movement. Additionally, patients with advanced disease experience pain at rest (i.e., ongoing pain)that is generally resistant to non-steroidal anti-inflammatory drugs (NSAIDs). Injection of monosodium iodoacetate (MIA) into the intra-articular space of the rodent knee is a well-established model of OA that elicits weight-bearing asymmetry and referred tactile and thermal hypersensitivity. Whether ongoing pain is present in this mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
128
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 114 publications
(137 citation statements)
references
References 41 publications
9
128
0
Order By: Relevance
“…PNB at the site contralateral to the injured hind paw did not result in CPP (Fig. S1), confirming that lidocaine at the dose used for PF injection does not produce systemic effects on pain relief, as demonstrated previously (23). These data suggest that relief of postsurgical, ongoing (i.e., spontaneous) pain is rewarding.…”
Section: Resultssupporting
confidence: 85%
“…PNB at the site contralateral to the injured hind paw did not result in CPP (Fig. S1), confirming that lidocaine at the dose used for PF injection does not produce systemic effects on pain relief, as demonstrated previously (23). These data suggest that relief of postsurgical, ongoing (i.e., spontaneous) pain is rewarding.…”
Section: Resultssupporting
confidence: 85%
“…Chronic neuropathic pain is an even better example. Although the loss-of-function TRPV1 variant I585V was reported to confer decreased risk for painful OA (Valdes et al, 2011), neither the selective TRPV1 antagonist AMG9810, nor the TRPA1 blocker HC-030031, ameliorated ongoing spontaneous pain in a model of advanced OA (Okun et al, 2012). Moreover, the TRPV1 antagonist ABT-116 failed to provide pain relief in client-owned dogs with hip OA (Malek et al, 2012), and a clinical trial with AZD1386 involving 241 patients with OA in seven different countries had to be terminated prematurely for lack of efficacy (Svensson et al, 2010;Miller et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Although we can not ascertain whether central or peripheral TRPV1 is the major contributor of mechanical hypersensitivity in our model, our findings with the intrathecal administration of the peptide support that spinal inhibition of TRPV1 channel enables pain relief in MIA-induced osteoarthritis. Of note, others have shown that antagonists of TRPV1 block MIA-induced thermal hyperalgesia but not weight asymmetry or ongoing pain (37). Finally, stimulation of capsaicinsensitive sensory neurons appeared to reduce both pain and bone lesions in the MIA model (42).…”
Section: Discussionmentioning
confidence: 99%